2023
DOI: 10.2196/45721
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Models for Sleep Quality Among College Students During the COVID-19 Outbreak: Cross-sectional Study Based on the Internet New Media

Abstract: Background COVID-19 has been reported to affect the sleep quality of Chinese residents; however, the epidemic’s effects on the sleep quality of college students during closed-loop management remain unclear, and a screening tool is lacking. Objective This study aimed to understand the sleep quality of college students in Fujian Province during the epidemic and determine sensitive variables, in order to develop an efficient prediction model for the early … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…More recently, a machine learning-based study was aimed to develop models for predicting sleep quality for university students during the COVID-19 pandemic and closed-loop management. 10 The study found that the pandemic had a detrimental effect on the sleep quality of college students. Eleven variables, including age, gender, residence, specialty, respiratory history, coffee consumption, stay up, internet usage, sudden changes, fears of infection, and closed-loop management, were identified as factors related to sleep quality in this study.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…More recently, a machine learning-based study was aimed to develop models for predicting sleep quality for university students during the COVID-19 pandemic and closed-loop management. 10 The study found that the pandemic had a detrimental effect on the sleep quality of college students. Eleven variables, including age, gender, residence, specialty, respiratory history, coffee consumption, stay up, internet usage, sudden changes, fears of infection, and closed-loop management, were identified as factors related to sleep quality in this study.…”
Section: Discussionmentioning
confidence: 98%
“…Eleven variables, including age, gender, residence, specialty, respiratory history, coffee consumption, stay up, internet usage, sudden changes, fears of infection, and closed-loop management, were identified as factors related to sleep quality in this study. 10 This study used logistic regression and three machine learning techniques to develop models, and among the four developed models, the artificial neural network model demonstrated the best performance in predicting sleep problems. 10 Nonetheless, the AUC value of the artificial neural network model was 0.713, indicating the accuracy of the model still needs improvements.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations